Penguatan Karakter Religius Peserta Didik di Era Digital: Tantangan dan Strategi Implementasi di Sekolah - Ballianie, Novia; Mardeli, Mardeli; Dewi, Mutia; Irawan, Bambang; Efriliyanti, Lia (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the strengthening of students’ religious character in the digital era in terms of challenges and implementation strategies in schools. The research employs a literature review method using secondary data sources, including textbooks, reputable national and international journals, conference proceedings, research reports, and educational policy documents. Data were collected through the inventory, selection, and documentation of relevant literature. Data analysis utilized content analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that strengthening students’ religious character in the digital era faces multidimensional challenges arising from technological developments and changes in social behavior. Exposure to digital content that is inconsistent with religious values, invalid religious information, and excessive gadget use weakens spiritual awareness, worship practices, empathy, and mutual respect. These conditions are exacerbated by predominantly cognitive-oriented learning, low digital literacy among educators, and inconsistencies in school religious culture. Therefore, strengthening religious character requires holistic, adaptive, and sustainable strategies within the context of modern education.